ANALISIS KINERJA STREAMING VIDEO MENGGUNAKAN MOBILE ADHOC NETWORK - Dipa Nusantara, Pualam (JURNAL LIMITS, 2023)
Mobile Ad Hoc Network is a Network made of several wireless mobile host that made a temporary Network anytime anywhere. Each node connected to the network will act as host as well as a router, there of each node must be willing to send a Package to the next node. Because of this, a routing Algorithm is needed to arrange the Mobile Ad Hoc Network test. This write up describes a network test that consists of 3 (three) test models or scenarios using the video conference technology. The parameter that will be calculated is the quality of service which will then be compared with the increase in the number of node.